Historical Dictionary of Russian Music - Jaffé, Daniel (Rowman & Littlefield Publishers, 2012)
Russian music today has a firm hold around the world in the repertoire of opera houses, ballet companies, and orchestras. The music of Pyotr Tchaikovsky, Nikolay Rimsky-Korsakov, Sergey Rachmaninov, Sergey Prokofiev, and Dmitri Shostakovich is very much today’s lingua franca both in the concert hall and on the soundtracks of international blockbusters from Hollywood. Meanwhile the innovations of Modest Mussorgsky, Alexander Borodin, and Igor Stravinsky have played their crucial role in the development of Western music in the last century, influencing the work of virtually every notable composer of the last century. The Historical Dictionary of Russian Music covers the history of Russian music starting from the earliest archaeological discoveries to the present, including folk music, sacred music, and secular art music. The book contains a chronology, an introductory essay, an extensive bibliography, and over 500 cross-referenced dictionary entries on every major composer in Russia’s history, as well as several leading composers of today, such as Sofia Gubaidulina, Rodion Shchedrin, Leonid Desyatnikov, Elena Firsova, and Pavel Karmanov. It also includes the patrons and institutions that commissioned works by those composers and the choreographers and dancers who helped shape the great ballet masterpieces. This book is an excellent access point for students, researchers, and anyone wanting to know more about Russian music.